Narcotics Suspect Pursuit Discretion: Testing Legality and Accountability in West Java Police Enforcement - Ibnu Mutsriadmoko; Haidan Angga Kusumah (Law and Justice research journal, 2026)
Pursuing narcotics suspects places police officers in rapid, risky, and rights-sensitive situations. Police law recognizes discretion, yet pursuit rules remain insufficiently detailed. This regulatory gap creates tension among effective narcotics enforcement, public safety, and accountability for coercive police conduct within the West Java Regional Police. This article analyzes the legality of pursuit discretion in narcotics cases and the legal accountability of narcotics investigators using normative and empirical perspectives. The study applies a juridical-empirical approach with descriptive-analytical specifications. Primary data were obtained through interviews, limited observation, and operational document review, while secondary data consisted of legislation, legal literature, court decisions, and institutional reports. Data were analyzed qualitatively through reduction, thematic categorization, source triangulation, and normative interpretation based on Philipus M. Hadjon's authority theory and Hans Kelsen's legal certainty theory. The findings show that pursuit discretion derives from statutory attribution under the Police Law and appears in four forms: deciding whether to pursue, selecting pursuit methods, using force, and assessing *in flagrante delicto* situations. However, the concepts of public interest and urgent necessity remain operationally vague, making the limits of authority and accountability insufficiently predictable. The study recommends a specific National Police Regulation on pursuit, scenario-based standard operating procedures, discretion and human-rights training, mandatory documentation, and coordinated internal and external oversight. The originality of this study lies in positioning narcotics pursuit discretion as an independent category of police action rather than merely part of arrest or firearms use.